Gembala dalam Pelayanan Pelepasan Okultisme - Mangoli, Yefta Yan (Pusat Studi Pentakosta Indonesia, 2023)
Occult release ministry is very important in pastoral ministry. However, the problem is that many pastors do not have sufficient ability and skills to solve the problems faced by the congregation, so that not a few members of the congregation prefer to go to psychics, even to traditional healers to find a way out of their problems. Lack of sense of responsibility of a pastor in ministry. Meanwhile, the church members really need the presence and role of a pastor in accompanying the church members in solving the problems they face. Servants of God or pastors do not take a personal approach to understand how to help church members get out of the struggles they are experiencing. This can cause congregation members to get involved in occultism. Using descriptive qualitative methods it can be concluded that in accordance with the results of studies conducted both through the Bible and books related to the topic of discussion that the ministry of releasing occultism is very important to be carried out by every pastor as a manifestation of responsibility in maintaining the life of the church members who are shepherded.AbstrakPelayanan pelepasan okultisme sangat penting dalam pelayanan penggembalaan. Namun yang menjadi persoalan adalah banyak gembala yang kurang memiliki kemampuan dan keterampilan yang cukup untuk menyelesaikan masalah-masalah yang dihadapi jemaat sehingga tidak sedikit dari warga jemaat yang lebih memilih pergi ke paranormal, bahkan ke dukun untuk mencari jalan keluar dari permasalahannya. Kurangnya rasa tanggung jawab dari seorang gembala dalam pelayanan. Sementara warga jemaat sangat membutuhkan kehadiran dan peran seorang gembala dalam mendampingi warga jemaat dalam menyelesaikan masalah yang dihadapi. Hamba Tuhan atau gembala kurang melakukan pendekatan secara pribadi untuk mengerti cara menolong warga jemaat keluar dari pergumulan yang dialami. Hal ini dapat menyebabkan warga jemaat untuk terlibat okultisme.Mengunakan metode kualitatif deskritif dapat disimpulkan bahwa Sesuai dengan hasil dari kajian yang dilakukan baik melaui Alkitab maupun buku-buku yang berkaitan dengan topik pembahasan bahwa pelayanan pelepasan okultisme sangat penting untuk dilakukan oleh setiap gembala sebagai wujud dari tanggung jawab dalam memelihara kehidupan warga jemaat yang digembalakan.